Islamizing The System of Economy: Solution Toward An Economical Welfare For The Islamic Landscape - Muhammad Iqbal Fasa (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
This paper attempts to offer Islamic economic system as the solution of the actualization of theeconomic welfare of ummah. It went from the failure of the capitalist economic system(capitalism) and socialist economic system (socialism) that causes the global crisis, even the fallof a country. The topics in the paper discusses in depth related to the cause of the failure of thecapitalist economic system (capitalism) and socialist economic system (socialism). Next, authorperform related in-depth analysis of the Islamic economic system is concerned withthe construction of the economic system of Islam; comparison of the characteristics of economicactivities that based on Islamic values with non-Islamic-based economic activities; comparingthe capitalist economic system, socialists and Islam; social institution in the Islamic economicsystem as a solution to alleviate poverty; and the implementation of Islamic economicsystem that cause the achievement of the financial system stability.